Media Representation of Female Politician Candidates in Social-Historian Context - Wulandari, Theresia Diyah; Ann Balaraman, Rani (Departemen Ilmu Komunikasi FISIP Universitas Atma Jaya Yogyakarta, 2025)
The 2024 direct elections in Indonesia failed to implement the affirmative action policy of 30 percent female representation in politics. This study examines how women are portrayed in campaign advertisements and media coverage. The aim is to identify the representation of female politicians within a socio-historical context. This research uses Ruth Wodak's critical discourse analysis method. Analysis of the 2024 election campaign shows that female politicians are not portrayed as competent figures in politics. This occurs due to several factors that hinder women from being elected as political leaders, including patriarchal culture, religious dogma, and gender bias.